Trend Inflation in the Japanese pre-2000s: A Markov-Switching DSGE - Ryo Kato; Junior Maih; Shin-Ichi Nishihama (Norges Bank, 2025)
In Japan, the inflation rate declined to near-zero, whereas the monetary policy faced a zero lower bound (ZLB) in the 1990s. We examine whether trend inflation had fallen to near-zero prior to the ZLB. To achieve this, we estimate Japanese pre-2000 trend inflation developing a Markov-switching New Keynesian dynamic stochastic general equilibrium (DSGE) model in which non-zero trend inflation is explicitly incorporated as a Markov chain state. Our estimation results indicate that (i) the trend inflation remained broadly stable at 3.0-3.5 percent from the 1960s to the late 1970s prior to the second Global Oil Crisis. (ii) Then, over time, trend inflation gradually declined to nearly 1.0 percent toward the Plaza Accord in 1985. (iii) Up until 1997 when the ZLB was hit, trend inflation hovered well above zero, mostly near 1.0 percent.
hdl:11250/3185073
Keywords: E31; E52; C54; 330; Trend Inflation; Markov-Switching Dynamic Stochastic Equilibrium Model; Deflation; Monetary Policy; Lost Decade of Japan